If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f + -3 = 15 Reorder the terms: -3 + f = 15 Solving -3 + f = 15 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + f = 15 + 3 Combine like terms: -3 + 3 = 0 0 + f = 15 + 3 f = 15 + 3 Combine like terms: 15 + 3 = 18 f = 18 Simplifying f = 18
| 2f+3=15 | | 2g=60+5g | | 7x=4x+18 | | 4*.25x-2=0 | | 2f-3=15 | | -2x+1+9x-5=7x-4 | | p+9=4p-12 | | (-(x-4)(x-4))=0 | | 8x-6+x-1=13 | | 3y=7+15 | | 8(k-3)=32 | | 4j-3j= | | (n+4)*9=72 | | 4s-13=15 | | (n-7)*3=12 | | 42x+3=43x | | (n+2)*5=20 | | 7x-1=3(x+2) | | 4a-1a=4 | | 4a-1a=4# | | 4-3(x+1)=10 | | 31x+4=128 | | -2(-x-4)=-2x+4 | | 9-3(2+y)=9 | | 8(4+y)=7(y-6) | | x+106=100 | | 260-5X=40X+20 | | p-2p=18 | | x^2-10x=-8 | | 1.005xn=2 | | 3x+2=-2x-28 | | 6(c+1)=5+5c |